1985
DOI: 10.1073/pnas.82.21.7419
|View full text |Cite
|
Sign up to set email alerts
|

Nasal absorption of insulin: enhancement by hydrophobic bile salts.

Abstract: We demonstrate that therapeutically useful amounts of insulin are absorbed by the nasal mucosa of human beings when administered as a nasal spray with the common bile salts. By employing a series of bile salts with subtle differences in the number, position, and orientation of their nuclear hydroxyl functions and alterations in side chain conjugation, we show that adjuvant potency for nasal insulin absorption correlates positively with increasing hydrophobicity of the bile salts' steroid nucleus. As inferred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(93 citation statements)
references
References 34 publications
4
88
1
Order By: Relevance
“…It has a vastly larger surface area (and thus a much larger potential absorptive surface) compared to the nasal, buccal, or rectal surfaces, sites that have been evaluated for administration of proteins (41,42). In this regard, the use of the lower respiratory tract may obviate the need to augment absorption per unit area, as has been suggested for the nasal epithelium using absorption enhancers such as bile salts, surfactants, or acrylic resins (43)(44)(45). Furthermore, unlike the gastrointestinal tract, the lower respiratory tract surface is not a hostile environment to proteins.…”
Section: Methodsmentioning
confidence: 99%
“…It has a vastly larger surface area (and thus a much larger potential absorptive surface) compared to the nasal, buccal, or rectal surfaces, sites that have been evaluated for administration of proteins (41,42). In this regard, the use of the lower respiratory tract may obviate the need to augment absorption per unit area, as has been suggested for the nasal epithelium using absorption enhancers such as bile salts, surfactants, or acrylic resins (43)(44)(45). Furthermore, unlike the gastrointestinal tract, the lower respiratory tract surface is not a hostile environment to proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of insulin absorbed also increases with increasing hydrophobicity of the bile salt. The order of bile salts' ability to increase insulin absorption is DCA>CDCA>CA>UDCA (Gordon et al 1985b). When sodium deoxycholate, the most hydrophobic bile salt, is co-administered with insulin, the absorbed insulin causes more than 30% reduction in blood glucose levels in diabetic subjects (Moses et al 1983).…”
Section: Nasal Absorptionmentioning
confidence: 99%
“…Large peptides such as insulin are not easily absorbed through the nasal mucosa when administered via a nasal spray (Hirai et al 1978). Insulin must be transported between or through the apical and basal membranes of columnar cells, basal cells and capillary endothelial cells of blood vessels ( Figure 5) (Gordon et al 1985a;Li et al 1992). However, it must first cross the mucous layer which varies in thickness averaging between 5 and 20 mm in depth.…”
Section: Nasal Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside their physiological role, micellar solutions of bile acids can solubilizate poorly soluble organic substances [5]. Furthermore, bile acids have a promoting effect in the transport of some polar drugs [6]. It has also been shown that the glycosylated derivates of bile acids facilitate transport of insulin and calcitonin through cell membrane [7].…”
Section: Introductionmentioning
confidence: 99%